Fonética e Fonologia: Perspectivas Complementares (Phonetics and Phonology: Complementary Perspectives) - Cristófaro Silva, Thaïs (Estudos da Língua(gem), 2006)
Este artigo avalia alguns aspectos das disciplinas denominadas fonética e fonologia. Inicialmente considera-se a visão dicotômica e separada das duas disciplinas. A seguir pondera-se sobre abordagens que integram a fonética e a fonologia como disciplinas análogas e complementares. As propostas teóricas da Fonologia de Uso (Bybee, 2001), da Teoria de Exemplares (Johnson, 1997) e algumas propostas teóricas de Pierrehumbert (2001) são avaliadas. Finalmente, consideram-se as conseqüências e desafios apresentados pela proposta de se integrar a fonética e a fonologia. PALAVRAS-CHAVE: Fonologia. Fonética. Léxico. Contraste. Variação sonora. ABSTRACT This article evaluates some aspects of the disciplines called Phonetic and Phonology. Initially we considered the dichotomy and separated vision of the two disciplines. To follow we pondered on boardings that integrates phonetic and the phonology as analogous and complementary disciplines. The theoretical proposals of the Frequency phonology (Bybee, 2001), Theory of Units (Johnson, 1997) and the some theorical proposals of Pierrehumbert (2001) are evaluated. Finally, we considered the consequences and challenges of the phonetic and the phonology integration. KEYWORDS: Phonetic. Phonology. Lexicon. Contrast. Sound variation.